2012
DOI: 10.1177/1049909112447285
|View full text |Cite
|
Sign up to set email alerts
|

Why do Palliative Care Patients Present to the Emergency Department? Avoidable or Unavoidable?

Abstract: Many ED presentations by palliative care patients may be avoidable. Appropriate sharing of information to on-call doctors, creating confidence in carers and providing extra practical supports is necessary. A comprehensive, coordinated specialist palliative care approach across community and acute services may help ensure patients are not sent to the ED inappropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 8 publications
7
82
2
7
Order By: Relevance
“…Although cancer is a chronic disease, patients with cancer often visit to ED because lifethreatening emergencies and unexpected side effects associated with cancer or treatment. Previous studies reported that lung cancer and advanced disease were most common causes of ED admissions of cancer (Rosenwax et al, 2011;Kraft-Rovere et al, 2012;Wallace et al, 2012;Gorham et al, 2013). Our study also showed similar results with previously studies.…”
Section: Discussionsupporting
confidence: 92%
“…Although cancer is a chronic disease, patients with cancer often visit to ED because lifethreatening emergencies and unexpected side effects associated with cancer or treatment. Previous studies reported that lung cancer and advanced disease were most common causes of ED admissions of cancer (Rosenwax et al, 2011;Kraft-Rovere et al, 2012;Wallace et al, 2012;Gorham et al, 2013). Our study also showed similar results with previously studies.…”
Section: Discussionsupporting
confidence: 92%
“…13,14 Informal caregivers may often feel uncomfortable or ill equipped to manage patients' symptoms at home. [13][14][15][16] Given that caregiving and symptom management are likely intertwined components of quality home hospice care, hospitalization may signify the fact that certain caregivers require more support. Research studying symptom management interventions in the home hospice setting is still sparse; however, interventions that incorporate new technologies or empower caregivers through education have had promising results.…”
Section: Discussionmentioning
confidence: 99%
“…It would not be unusual to find patients in a hospital setting with a high symptom burden during a period of acute illness and in fact this is often what precipitates an admission to hospital. 4 In view of the fact that the hospital setting is often criticised as being poorly prepared to provide adequate symptom control at the end of life 59,60 exploring the effectiveness of symptom management may be more useful.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Hospitals are often the setting where a life limiting diagnosis is made and where patients present when symptoms develop or when they are not well managed. 4 Furthermore for people with illnesses such as chronic obstructive pulmonary disease and congestive cardiac failure, hospitals provide episodic care over many years for illness exacerbations during which death could occur. 5 In most developed countries, hospitals are also the setting in which most people will die.…”
Section: Introductionmentioning
confidence: 99%